Determination of Production Targets on Sewing for the Front Body of H&M Pajamas Jogger Pants - Afriani Kusumadewi; Filly Pravitasari; Feny Nurherawati (Sainteks: Jurnal Sain dan Teknik, 2022)
The process of sewing the front body of an order for H&M Pajamas Jogger Pants has a fairly high quality, but the target for setting production targets is based on experience and estimates only. The setting of a fairly high production target of 640 pcs/day is often not achieved because the determination of the production target is not based on the level of difficulty of the work carried out by the operator (easy, medium, or difficult), the operator's skill as well as the condition of the machine used in the process. condition is good or not, so that the target set is often not achieved because it is not in accordance with the condition of the operator's ability in general. Based on the observation of the operator's working time measurement, the total standard time for the 26 manufacturing processes for the front body component of the order of H&M Pajamas Jogger Pants was 23,029 minutes. After getting the total standard time for making the front body component of the order for these H&M Pajamas Jogger Pants, a new production target can be determined, which is 542 pcs/day. This new production target is made to represent the general working conditions of operators and has taken into account the factors of slack, work fatigue and other unavoidable obstacles.